Density cavity formation through nonlinear interaction of 3‐D inertial Alfvén wave and ion acoustic wave. Issue 12 (19th December 2014) - Sharma, R. P.; Yadav, N.; Pathak, N.
Abstract Density cavities having transverse‐scale size of the order of electron inertial length have been observed in auroral ionosphere by Freja spacecraft. In the present study, density cavity formation in auroral regions has been investigated using numerical simulation techniques. Nonlinear interaction of inertial Alfvén waves and ion acoustic waves has been suggested as a possible mechanism to apprehend density cavity formation in auroral regions. In the proposed mechanism, strong modification in the density profile takes place due to the ponderomotive force of inertial Alfvén waves and accounts for these density depleted regions. In literature also, it has been demonstrated that these cavities are associated with the ponderomotive forces of inertial Alfvén wave. Our presented model also attempts to understand the salient features of auroral density cavities which are reported in literature from the analysis of data available from FAST spacecraft. Relevance of obtained results with observations in auroral ionosphere has also been discussed.